Blood infernal - Rollins, James, 1961- (Rollins, James, 1961- Order of the Sanguines series., 2015)
"The third installment in the bestselling gothic series, about an ancient order who speak the truth behind Christ's miracles and strive to protect the world from evil from New York Times bestselling authors James Rollins and Rebecca Cantrell"--